A Mild and Efficient Synthesis of Pyrazolo[1,5-a]pyridines Mediated by Triphenylphosphine/Diiodine - Jia, Kai; Ma, Wenchao; Yan, Yintao; Zhang, Chenming; Jiang, Chao (Synlett, 2021)
A synthesis of 2,3-diaryl-substituted pyrazolo[1,5-a]pyridines in moderate to good yields under metal-free and mild conditions is described. The intramolecular cyclization of the oxime substrates is mediated by PPh3/I2, which leads directly to pyrazolo[1,5-a]pyridines without the formation of a 2H-azirine intermediate. Various substituents on the aryl rings are compatible with the method.
Keywords: pyrazolopyridines; oximes; metal-free synthesis; iodine; triphenylphosphine